Aktivitas Pelapukan Kayu Inokulum Ganoderma boninense pada Tumpangsari Bibit Kelapa Sawit dan Talas-Talasan - Monica Alesia; Suwandi Suwandi; Suparman Suparman (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2021)
Basal stem rot of oil palm caused by Ganoderma boninense is difficult to be controlled due to abundance of inoculum sources in the field. This study was aimed to determined effects of taro plants viz. Belitung taro (Xanthosoma sagittifolium), Bogor taro (Colocasia esculenta), and Japanese taro (Colocasia esculenta var. antiquorum) on decay of G. boninense inocula. Pathogen inocula as rubber wood block (RWB) colonized by G. boninense was attached with main roots of oil palm seedling and buried into soil of oil palm seedling (monoculture), mixed planting of oil palm and taro plants, or of taro plants monoculture. Burying of pathogen inocula for 3 and 6 months on taro plant resulted in 2.1 times higher decay of RWB compared than oil palm monoculture. Increasing of decay also exhibited on mixed cropping system, but it was slightly lower than on oil palm monoculture. This result suggesting the benefit of taro plants either planted under monoculture or mixed cropping to fasten decomposition of infected wood debris as an inoculum source of G. boninense.